An improved numerical integration algorithm for elastoplastic constitutive equations. (March 2015) - Cecílio, Diogo L.; Devloo, Philippe R.B.; Gomes, Sônia M.; dos Santos, Erick R.S.; Shauer, Nathan
Abstract: A simplified methodology is proposed for elastoplastic calculations which holds for associative models. It is based on the representation of the elastoplastic model based on a rotation of the principal stresses and the fact that, in such system of coordinates, the direction that minimizes the square of a distance between a trial stress and the plastic surface has the same direction as the plastic deformation evolution. Such an approach allows for the elastoplastic calculation of complex models to be simpler and more efficient computationally. The proposed methodology is verified by the application to the elastoplastic model of Sandler–DiMaggio.